Parental Feeding Styles and Their Association With Complementary Feeding Practices and Growth in Mexican Children - Kim-Herrera, Edith Y.; Ramírez-Silva, Ivonne; Rodríguez-Oliveros, Guadalupe; Ortiz-Panozo, Eduardo; Sánchez-Estrada, Marcela; Rivera-Pasquel, Marta; Pérez-Escamilla, Rafael; Rivera-Dommarco, Juan Angel (Frontiers in Pediatrics, 2021)
Background: Complementary feeding practices and corresponding parental feeding styles influence nutritional status in later stages of childhood. Findings on the association of these variables with infant growth remain inconsistent; in Mexico, a research gap exists in this area. Research Aims: (1) To characterize parental feeding styles and complementary feeding practices, and (2) to evaluate the association of parental feeding styles with complementary feeding practices and infant growth at six and nine months of age. Methods: Data were collected from a prospective Mexican birth cohort. Parental feeding styles, complementary feeding practices, and anthropometric data from 263 and 234 mother-child pairs (infants of six and nine months of age, respectively) were analyzed. Logistic and linear regression models were used to determine the associations between variables. Results: The predominant parental feeding style was the “responsive style” (90%). Only 43.7% and 8.1% of six- and nine-month-old infants, had adequate complementary feeding practices respectively. At six months, mothers who were responsive to satiety signals had 11% lesser possibilities (OR=0.89, 95% CI [0.80, 0.98]) of their infant having inadequate complementary feeding practices than their counterparts and “pressuring to finish” and “pressuring to eat cereal” sub-constructs were associated with lower weight for length and body mass index Z-scores (p=0.02). Conclusions: A high proportion of infants (>40%) did not meet international recommendations. The “pressuring” parental feeding style sub-constructs were associated with growth indicators in six-month old infants. This emphasizes the importance of promoting parental responsiveness to infant appetite and satiety signals to achieving adequate complementary feeding practices.